Poly(I:C) exposure during in vitro fertilization disrupts first cleavage of mouse embryos and subsequent blastocyst development. (June 2022) - Wang, Zhicheng; Chen, Shiyi; Zhang, Yan; Su, Changqi; Liao, Yonglan; Zhang, Shilin; Ren, Yan; Ye, Fei; Zeng, Changjun; Zhou, Guangbin; Xian, Hong; Zhang, Ming
Abstract: The reproductive system can be infected by a variety of double-stranded RNA viruses, which disrupt ovary function and pregnancy. However, whether viral infection directly affects early embryonic development remains unknown. Here we show that Poly(I:C), which mimics a double-stranded RNA virus, significantly impaired mouse early embryonic development in vitro, and up-regulated TLR3 and IFNα at the two cells embryo stage. Further studies indicated that Poly(I:C)-treatment caused DNA damage and abnormal spindle morphology at the first cleavage. Moreover, CDX2 and SOX2 expression was decreased while blastocyst cell apoptosis was increased. Altogether, Poly(I:C) decreased the rate of successful in vitro fertilization via DNA damage and abnormal spindle morphology at the first cleavage and inhibited early embryonic development by inducing immune response and promoting blastocyst cell apoptosis. This study provides an implication for exploring the causes of reproductive disorders in mammals and humans caused by infection of double-stranded RNA virus. Highlights: Poly (I:C), the pathogenic molecular pattern of dsRNA) viruses, reduces IVF and blastocysts development. Poly (I:C) causes DNA damage and disrupt spindle morphology, assembly and remodeling, and induces immunoresponse. Poly(I:C) impair blastocyst development by disturbing proliferation and differentiation and inducing cell apoptosis.